Plan de políticas internas de créditos y cobranzas y su incidencia en la recuperación de cartera de la fundación espoir "mi bankito" cantón Quevedo año 2014 - Estrada Verdesoto, Carmen del Rocío (2015)
This research has as main purpose to develop a plan of internal credit and collection policies to improve the recovery of portfolio Espoir "my bankito" Foundation in the canton Quevedo, the goal is to apply to the branch of a plan policies to help the management processes taking place internally in order to provide a quality service to all its customers. The Espoir "my bankito" Foundation is an institution that has been characterized for being responsible in their commitment to loyalty and solidarity in the service of the community in the provision of microcredit business, health and strengthening emerging Canton production rates and therefore the country. However in recent times have presented problems in their fee policies and portfolio recovery to be maintained, the goal is to develop a plan of internal policies to improve administrative processes agilitando loans and has no impact on your financial portfolio to when recovering resources. It is intended to apply an analysis to diagnose which are the main problems faced by users not to cancel their credit obligations to implement policies that help solve these problems. They plan to examine the domestic political environment of the institution observing their weaknesses and strengthen their threats to turn them into market opportunities were used. To attract more users and that customer are satisfied with the services that are being provided.